THE PROBLEMS IN TEACHING SPEAKING SKILL AT SMP ADABIYAH PALEMBANG - Agustina Maharani; Husnaini Husnaini (EXPOSE (Journal of English Education and for Specific Purpose), 2023)
The aims of this study was to find out the problems faced by the English teachers’ in teaching speaking skill at SMP Adabiyah Palembang and how the teachers overcome these problems. This study applied qualitative research with a case study as the research design. The participants of this study were three English teachers taken by using total sampling technique. Interview was conducted to collect the data and the data from interview were analyzed by using thematic analysis. The findings showed that there were seven problems faced by English teachers in teaching speaking skills: (1) the influence of native language during the teaching and learning process; (2) lack of teachers ability in selecting the appropriate speaking material based on the students’ age; (3) the influence of students’ innate phonetic ability; (4) having difficulties in controlling the students’ language ego; (5) lack of teachers ability in building students’ motivation in speaking; (6) difficult in handling the large class; and (7) the interference of school facilities in teaching and learning process. In brief, these problems made teaching and learning did not run effectively,